Pengaruh Penggunaan Media Pembelajaran Berbasis Powerpoint Terhadap Keaktifan Belajar Siswa Kelas X Di SMA N 2 Medan - Fais Irawan; Rejosu Vanhot Sianturi; Adelia Marta Lubis; Excaudia Siringoringo; Revita Yuni (Insan Zenius Ilmiah, 2025)
This research aims to determine the extent to which the use of PowerPoint-based learning media influences the learning activity of 10th-grade students at SMA Negeri 2 Medan. This research is motivated by the importance of learning media that can make the learning process more engaging, interactive, and easier for students to understand. The approach used is quantitative with the simple linear regression method to analyze the relationship between the use of PowerPoint media and students' learning activity levels. The research sample consisted of 32 tenth-grade students selected using the total sampling technique. The research instrument, a questionnaire, has been tested for validity and reliability, and all items have been declared suitable for use. The research results indicate that using PowerPoint media has a positive and significant impact on student learning activity. This is evidenced by a calculated t-value of 2.695, which is higher than the table t-value of 1.69726, and a significance value of 0.011, which is less than 0.05. The coefficient of determination value of 0.195 indicates that 19.5% of the variation in student learning activity is influenced by the use of PowerPoint media. Thus, it can be concluded that PowerPoint-based learning media is effective in increasing student activity because it can present material visually, attractively, and in an easier-to-understand manner, thereby encouraging students to be more involved in the learning process.